Exploring the effect of play on heart rate variability as a measure of positive emotional states in pigs - Steinerová, Karolína; Krause, Annika; Parker, Sarah E.; Seddon, Yolande M. (Frontiers in Veterinary Science, 2025)
Play behaviour has been suggested to be inherently rewarding for animals, inducing positive emotional states. The psychophysiological effect of emotions can be assessed through heart rate variability (HRV), serving as a proxy measure of sympathovagal balance. This study investigated how the performance of play influences heart rate (HR) and HRV parameters (RMSSD, SDNN) in pigs. It was hypothesized that HRV would increase during and immediately after play due to predominant vagal activation compared to baseline, indicating a positive emotional state. Gilts (n = 32, 18 and 19 weeks of age), housed in standard partly-slatted pens, were selected from two pen-level play treatments: Novelty (NOV) and Play Pen (PLP). Play treatment pigs were reared with intermittent play promotion (3x/week) from 10 weeks of age. For HRV recordings, play was promoted for 15-min in pairs of gilts within treatment, with destructible novel objects given either in the home pen (NOV, 1 m2/pig), or in an enclosed ‘playpen’ area providing extra space (PLP, 2.9 m2/ pig). HRV was measured during a play session in three consecutive periods: (i) baseline (before play bout, no play occurring), (ii) play bout (play expression), and (iii) after-play (immediately after play bout). Twenty-six gilts played at least once. Play bouts lasted between 10 and 30 s (10 s: n = 60, 20 s: n = 18, 30 s: n = 6). In 10-s bouts, compared to baseline, RMSSD was higher during play (p = 0.027) and after-play (p = 0.015), while SDNN increased during play (p ≤ 0.001) and after-play (p = 0.008) only with ambulation (pig moving forward: walking or running). HR did not differ across periods but was higher at ambulation (p = 0.003). Twenty-sec bouts followed the same relationship with only numerical differences, while HRV in 30-s bouts did not differ. Treatments did not influence HRV. Results suggest that engaging in play increases HRV, with this effect persisting into the period immediately after play. This indicates that play contributes to positive emotional states in pigs. Physical activity involved in play influences HRV. More dynamic and energetic play involving ambulation might be more rewarding for pigs. This study provides evidence for assessing positive emotions in pigs and underscores the importance of incorporating rewarding experiences into conventional farming practices.